96 Cerebral hemodynamics and microcirculatory function in Swedish patients with systemic lupus erythematosus. (April 2019) - Sjöwall, Christopher; Svensson, Christina; Jonasson, Hanna; Strömberg, Thomas; Bergstrand, Sara; Eriksson, Per; Zachrisson, Helene
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory disease characterized by multiple organ involvement. Atherosclerosis is the underlying cause for SLE-related cardiovascular disease, and reliable non-invasive methods for early detection of vascular involvement, including microcirculatory assessment, is important. The aim of this study was to detect whether macro- and microcirculation is impaired in patients with SLE. Methods: Fifteen patients classified with SLE according to the 2012 SLICC criteria (mean age 51.4 years) with moderate atherosclerotic ultrasound findings in common carotid artery, and 15 age- and sex-matched and plaque-free population controls, (mean age 51.7) were investigated. Intima-media thickness (IMT) was recorded with high frequency ultrasound (GE Logic E9) in carotid and central arteries. Microcirculatory oxygen saturation and endothelial function were assessed with EPOS (Enhanced Perfusion and Oxygen Saturation) (PeriFlux 6000, Perimed, Järfälla, Sweden) and EndoPATTM2000 system (Itamar Medical, Israel). The EPOS system measures red blood cell tissue fraction, speed resolved perfusion and oxygen saturation in the microcirculation of the skin. EndoPAT 2000 records changes in finger arterial pulsatile volume reflecting microcirculatory endothelial function. Cerebrovascular reserve capacity was assessed by Transcranial Doppler (TCD) (Sonara TCD (Natus) by detecting mean flow velocities in middle cerebral artery at base-line and after 30 s of breath holding. A breath-hold-index (BHI) of <0.69 indicates impaired cerebrovascular reserve capacity. Results: IMT in the aortic arch was higher in patents versus controls, 1.3±0.3 vs 1.1±0.2 mm (p=0.04), whereas no difference was found in the common carotid artery, 0.61±0.13 vs 0.55±0.10 mm (p=0.2). BHI-values were lower in the SLE-group, 1.29±0.36 vs 1.65±0.56 (p=0.05), whereas both groups had signs of preserved cerebrovascular reserve capacity. Mean oxygen saturation peak was decreased in SLE patients versus controls, 79.5±7.8% vs 86.9±5.6% (p=0.006). Endothelial function using EndoPAT did not differ, 0.72±0.40 vs 0.84±0.24, (p=0.3). Conclusions: This study indicates that microcirculatory vessel disease, as measured with EPOS and breath-hold index, could be present in SLE cases with atherosclerotic findings. However, the impaired microcirculation in SLE compared to population controls needs further validation in larger patient groups, also including non-atherosclerotic cases with SLE. Funding Source(s): This work was supported by grants from the Swedish Rheumatism Association, the County Council of Östergötland, the Swedish Society of Medicine, the King Gustaf Vs 80 year anniversary foundation and the King Gustaf V and Queen Victorias Freemasons foundation.